The cognitive interview: inexperienced police officers' perceptions of their witness/victim interviewing practices - Dando, Coral (Legal and criminological psychology, 2008)
Purpose. The primary objectives of the study reported here were twofold. First, to investigate less experienced frontline police officers' perceptions of their witness interviewing practices with specific reference to their use of the ten cognitive interview components taught during initial PEACE (a mnemonic for the stages of the interview; Planning and preparation, Engage and explain, Account, Closure and Evaluation) interview training. Second, to investigate this group of officers' practical experiences of interviewing witnesses. Method. A sample of 221 young, in-service, non-specialist police officers from five UK police forces completed a self-report questionnaire concerning their perceived witness interviewing practices. Respondents were surveyed about their use of the PEACE cognitive interview components, their practical experiences of interviewing witnesses and victims, and their views on investigative interviewing training. Results. There was a consensus among these officers that they perceived using some of the PEACE cognitive interview components more frequently and perceived some of them to be more effective than others. Conclusion. This study provides a unique insight into the perceived interviewing practices of some of the least experienced and the least trained investigative interviewers who conduct the majority of frontline witness interviews. These officers report feeling inadequately trained, under pressure and generally ill equipped to conduct a PEACE cognitive interview.